Case report: Traumatic carotid artery dissection after 7D High-Intensity Macro- and Micro-Focused Ultrasound treatment for skin laxity of the neck - Du, Fenghe; Shao, Jiang; Lai, Zhichao; Li, Kang; Wang, Chaonan; Liu, Bao (Frontiers in Cardiovascular Medicine, 2022)
Background Trauma is a relatively uncommon etiology of carotid artery dissection. Trauma is both penetrative and trivial, which can lead to carotid artery dissection. In the current study, we present an unusual case in which carotid artery dissection was potentially triggered by the damaging thermal effect of 7D High-Intensity Macro- and Micro-Focused Ultrasound (7D HIFU), which has been proposed as a safe and effective non-surgical modality for skin rejuvenation. Case summary A 41-year-old woman developed headache and clinical manifestations of cerebral infarction after 7D HIFU, aimed at removing neckline. Head and neck magnetic resonance angiography (MRA) and computed tomography angiogram (CTA) revealed severe stenosis and dissection of the left internal carotid artery. Neither the patient's history nor the physical examination showed any special indicators. After resection of the left carotid artery dissection, autologous great saphenous vein interposition grafting, and simple mastoidectomy, the patient underwent head and neck MRA, which revealed recanalization of the left internal carotid artery. Conclusion Although mild or moderate complications of 7D HIFU, such as erythema, edema, transient dysesthesia, and motor nerve paresis, have been previously reported, a few previous literature studies documented severe complications of the cosmetic procedure. However, many recent studies pointed out the possibility of 7D HIFU damaging adjacent non-target tissues due to inadequate focal depth of HIFU treatment. Our case is the first to indicate that 7D HIFU could cause carotid artery dissection. We propose that better visualization systems and more rigorous operator training are needed to reduce the risk of the potential off-target damaging effect of 7D HIFU by reporting the case in which the damaging heat effect of 7D HIFU precipitated the carotid artery dissection HIFU.